PEMBINAAN SIKAP MENTAL SISWA MELALUI PENDIDIKAN AGAMA ISLAM PADA SMAN DI KABUPATEN BIREUEN - Iskandar; Jamaluddin Idris; Warul Walidin Ak (FITRAH: International Islamic Education Journal, 2021)
This dissertation is entitled: â€œFostering Students' Mental Attitude Through Islamic Religious Education at Senior High School in Bireuen Regencyâ€.The teacher is a figure who is expected to be able to provide enlightenment and coaching in student behavior. The teacher plays an active role in developing the potential for the formation of students' morals, so students can distinguish between good and bad according to reason and norms that exist in the environment in which students are located. Moral development must start at the school level, so students have a strong foundation in daily behavior. This research uses a qualitative research method with a descriptive qualitative approach. The results showed that; Islamic Religious Education teachers encourage students to learn to understand the values â€‹â€‹of the teachings of Islam have been done correctly. Learning Islamic Religious Education, students are taught to think patterns with intelligence to manage emotionally, spiritually, patiently, diligently in learning, sincerity, sincerity, tolerance and totality. Fostering the Islamic aqidah, the recitation of the Qur'an and tausiah, dhuha prayer, dhuhur prayer in congregation for students. Coaching Akhlaqulkarimah, the teacher provides awareness and habituation includes; good attitude, good manners in words, always cover genitalia when being outside school.